Provocation Through ISO 9001 Certification: What is the Most Significant to Output Quality, Quality Awareness or Procedure Documentation? - Ernawati, Erni (Journal of Emerging Business Management and Entrepreneurship Studies, 2023)
This research aimed to identify the most significant changes that occur to employees and organizations when the company has obtained ISO 9001 certification and examine how these changes affect output quality. This study used a mixed method, combining The Most Significant Change (MSC) and Structural Equation Model (SEM) analysis techniques. This research was conducted in a printing company in Jakarta, Indonesia. This was carried out from January to March 2023. The MSC analysis technique involved 3 informants, and 100 data respondents involved in a survey related to filling out the questionnaire. After the company (BOS) received ISO 9001 certification, the MSC results were quality awareness and procedure documentation. Both showed a positive and significant effect on output quality. Documentation of procedures showed a greater influence than quality awareness. However, Quality Management Practices as a moderator variable were proven to be able to increase the effect of quality awareness on output quality. Further research can broaden this scope by surveying respondents of different organizations so that generalization is increased.